2013
DOI: 10.1038/ijo.2013.188
|View full text |Cite
|
Sign up to set email alerts
|

Mutation screen of the SIM1 gene in pediatric patients with early-onset obesity

Abstract: In this study, we have demonstrated the presence of rare SIM1 variants in both an obese pediatric population and a population of lean adult controls. Further, we have shown that functional in vitro analysis of SIM1 variants may help in distinguishing benign variants of no pathogenic significance from variants which contribute to the obesity phenotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 31 publications
1
25
2
Order By: Relevance
“…Loss-of-function variants in SIM1 may cause human obesity with or without PWS-like features. [37][38][39][40] However, in our study, SIM1 deletions in patients no. 5, 11, 12, and 13 were not associated with obesity.…”
Section: Cytogenetic and Molecular Resultscontrasting
confidence: 57%
See 2 more Smart Citations
“…Loss-of-function variants in SIM1 may cause human obesity with or without PWS-like features. [37][38][39][40] However, in our study, SIM1 deletions in patients no. 5, 11, 12, and 13 were not associated with obesity.…”
Section: Cytogenetic and Molecular Resultscontrasting
confidence: 57%
“…51 Some patients with SIM1 loss-of-function variants have cognitive impairments and/or behavioural disorders. [38][39][40] However, none of those described to date had a history of neonatal hypotonia or feeding difficulties early in life. 38 Recently, a statistically significant association was demonstrated between the SIM1 SNP rs3734354 (Pro352Thr) and language impairment.…”
Section: Cytogenetic and Molecular Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, common variations in SIM1 were shown to be significantly associated with the variation of body mass index (BMI) in Pima Indians (12), while the association was far less marked in Europeans (13). Recently, we and others have demonstrated that rare loss-of-function mutations in SIM1 cause severe obesity in European individuals (14)(15)(16). In particular, we described eight heterozygous SIM1 substitutions in four obese children presenting with PWLS and in seven morbidly obese adults (14).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Ramachandrappa et al identified 13 heterozygous SIM1 substitutions in 28 unrelated severely obese patients, of which seven (p.S71R, p.R171H, p.L238G, p.P497R, p.S550L, p.D707H, and p.T712I) significantly reduced transcriptional activity of SIM1 and cosegregated with obesity in families with variable penetrance (15). Finally, Zeghers et al reported two loss-offunction mutations (p.T481K and p.A517V) in two obese patients, without any details on their cognitive status (16). Overall, these studies demonstrated the strong contribution to obesity of rare loss-offunction mutations in SIM1 (14-16), yet the role of these mutations in developmental delay remained unclear.…”
Section: Introductionmentioning
confidence: 99%